Lisbon brand image perception: the perspective of tourists - Miranda, Sandra (2020)
Artigo baseado na apresentação para o ICIEMC - International Conference on Innovation And Entrepreneurship in Marketing and Consumer Behavior: Projecting the Future, the Future Is Now! Realizado, online, na Universidade Aveiro, 12-13 novembro de 2020